New directions in American politics - La Raja, Raymond J., 1965- (New directions in American politics, 2013)
"New Directions in American Politics brings together top scholars to write original essays across the standard curriculum of American government and politics, capturing emerging research in the discipline in a way that is accessible for undergraduates. Each chapter combines substantive knowledge with the kind of skill-building and analytical inquiry that is being touted at top universities across the country. Contributors to New Directions highlight why the questions they seek to answer are critical for understanding American politics, and situate them in the broader context of controversies in research. The book will introduce students to how political science works, in addition to how our political system works. The teaching of American politics follows a well-worn path. Textbooks for introductory courses hew to a traditional set of chapters that describe the Founding, American institutions, the ways citizens participate in politics, and sometimes public policy. The material rarely engages students in the kind of questions that animate scholarship on politics. One hurdle for instructors is finding material that reflects quality scholarship--and thus teaches students about why, not just what--and yet is accessible for undergraduates. Articles in scholarly journals are typically unsuited for undergraduate courses, particularly introductory courses. What is needed is a book that conveys exciting trends in scholarship across vital topics in American politics and illustrates analytical thinking. New Directions in American Politics is that book and will be an ideal companion to standard textbooks that focus mostly on nuts and bolts of politics"--